2019
DOI: 10.1080/09650792.2019.1626753
|View full text |Cite
|
Sign up to set email alerts
|

Questioning personal tutoring in higher education: an activity theoretical action research study

Abstract: Do w nlo a d e d fro m: h t t p://i n si g h t. c u m b ri a. a c. u k/i d/ e p ri n t/ 4 1 0 9/ U s a g e o f a n y i t e m s f r o m t h e U n i v e r s i t y o f C u m b r i a' s i n s t i t u t i o n a l r e p o s i t o r y 'I n s i g h t' m u s t c o n f o r m t o t h e f o l l o w i n g f a i r u s a g e g u i d e l i n e s .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The positive experience data described communications and structures that worked for the students, and a congruence between levels of authentic engagement of staff in the act of care and the perceived role of the personal tutoring. This accords with previous empirical work on student perceptions of personal tutoring (Yale, 2019a;Stuart, Willocks and Browning, 2019) which showed that having a negative experience of personal tutoring is worse than having none. The negative experience data surfaced strong feelings in relation to the perceived utility of the activity and the sincerity of the offering of personalised support.…”
Section: Design Considerations For a Successful Personalised Support ...supporting
confidence: 91%
See 3 more Smart Citations
“…The positive experience data described communications and structures that worked for the students, and a congruence between levels of authentic engagement of staff in the act of care and the perceived role of the personal tutoring. This accords with previous empirical work on student perceptions of personal tutoring (Yale, 2019a;Stuart, Willocks and Browning, 2019) which showed that having a negative experience of personal tutoring is worse than having none. The negative experience data surfaced strong feelings in relation to the perceived utility of the activity and the sincerity of the offering of personalised support.…”
Section: Design Considerations For a Successful Personalised Support ...supporting
confidence: 91%
“…This finding is well known (e.g. Stuart, Willocks and Browning, 2019;Tett et al, 2017;Stephen et al 2008;). However, the perception of whether this care was genuine, was also clearly evidenced in the data (see next section).…”
Section: Attitudes and Tutor Knowledgesupporting
confidence: 72%
See 2 more Smart Citations
“…However, the existing personal tutoring system, reported a British University, has for quite some time been in need of review and improvement, as evidence suggests that it is ineffective [3,4]. The findings raise implications for the formulation of institutional policies for conducting university tutoring and e-learning to improve student experiences [5]; an aspect that is supported by the numerous studies that have shown the effectiveness of tutors on students [6].…”
Section: Introductionmentioning
confidence: 87%